2010
DOI: 10.1007/s00534-010-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified splenocaval shunt plus devascularization on esophagogastric variceal bleeding: a comparative study of this treatment and devascularization only in cirrhotic portal hypertension

Abstract: The modified splenocaval shunt plus PCDV is a safe and effective procedure for the long-term control of variceal bleeding; the procedure may not only maintain the portal flow to the liver, but may also protect the liver function in cirrhotic patients. The better clinical outcome means that the procedure may be one of the best choices for treating portal hypertension of cirrhotic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The 3-year survival rate of patients who underwent traditional devascularization was 95.52% according to Yang et al [ 16 ], while Lu et al [ 17 ] reported a 5-year survival rate of 86% and a rebleeding-free rate of 84.8%. Du et al [ 18 ] showed that the 1-year, 3-year, and 5-year survival rate was 96.7%, 83.3%, and 73.3%, respectively. None of the 54 patients in the study by Zheng et al [ 19 ] had a rebleeding event during the follow-up period (3–36 months), and in another study by Zhou et al [ 20 ], no deaths were reported in a mean of 25 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-year survival rate of patients who underwent traditional devascularization was 95.52% according to Yang et al [ 16 ], while Lu et al [ 17 ] reported a 5-year survival rate of 86% and a rebleeding-free rate of 84.8%. Du et al [ 18 ] showed that the 1-year, 3-year, and 5-year survival rate was 96.7%, 83.3%, and 73.3%, respectively. None of the 54 patients in the study by Zheng et al [ 19 ] had a rebleeding event during the follow-up period (3–36 months), and in another study by Zhou et al [ 20 ], no deaths were reported in a mean of 25 months after surgery.…”
Section: Discussionmentioning
confidence: 99%